Pendampingan Perencanaan dan Pengawasan Pembangunan Gedung Kelas Tiga Lantai Pondok Al Firdaus Kemiling Bandar Lampung - Rajiman Rajiman; Dian Perwita Sari (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2026)
The limited availability of learning spaces at Pondok Al Firdaus Kemiling, Bandar Lampung, requires technical assistance so that the construction of a new three-story classroom building can be implemented safely and systematically. This community service program aimed to assist the partner in preparing planning concepts, cost estimates, work schedules, and supervision instruments for quality and occupational safety. The method included coordination of spatial needs, existing-condition surveys, preliminary design assistance, budget and scheduling guidance, structural work supervision, and evaluation using observation, checklists, and pre-test/post-test instruments. The program produced preliminary planning documents and inspection checklists for foundation, column, beam, slab, and safety works. The construction committee’s understanding of drawings, quantities, cost, time, quality, and safety increased from an average score of 56.25 to 84.50. This assistance helped the partner reduce the risk of work errors, cost inefficiency, and quality nonconformity. The program confirms that civil engineering expertise from universities can strengthen community-based educational facility development in a more accountable and sustainable manner.